PEMODELAN SISTEM HIDROPONIK APUNG, SEBAGAI UPAYA BUDIDAYA TANAMAN SAYURAN DAUN, DI WILAYAH PESISIR TERDAMPAK ROB DAN SALIN - Ari Handriatni (LPPM Universitas Pekalongan, 2021)
Vegetable plants are plants that are popular with people, apart from tasting good when cooked, they can also be used as fresh vegetables, containing nutritional values, such as vitamins and minerals. This study aims to obtain a modeling system for leaf vegetable cultivation in coastal areas inundated by rob and saline and a formula to suppress extreme climatic conditions. The research method is a qualitative descriptive method, based on data from several research results. From several previous research results, it shows that the cultivation of leaf vegetables in coastal areas inundated by rob and saline can be overcome by modeling a floating hydroponic system, a formula for suppressing extreme climates using a nutrient concentration of 2000 ppm, media of husk or rockwall charcoal, wicks with cloth. flannel, the type of nutrition using AB mix Goodplant and the number of seeds of one seed per hole. Types of leafy vegetables that are suitable are kale and pakcoy. The variables observed included the growth components of leaf vegetable plants which showed very significant differences in the treatment given.